1995
DOI: 10.1099/13500872-141-4-1017
|View full text |Cite
|
Sign up to set email alerts
|

Physiological roles of leupeptin and extracellular proteases in mycelium development of Streptomyces exfoliatus SMF13

Abstract: Streptomyces exfoliatus SMF13 produced leupeptin, chymotrypsin-l i ke protease (CTP), metalloprotease, and trypsin-like protease (TLP) extracellularly. The activity of TLP was specifically inhibited by leupeptin. Production of leupeptin was closely associated with growth but leupeptin was inactivated by leupeptin-inactivating protein (LIP) when growth reached the stationary phase in submerged cultures, or when aerial mycelia started to form on surface cultures. Autolysis of mycelia after the stationary phase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 15 publications
3
45
0
Order By: Relevance
“…Temperature is an important environmental factor for growth and enzyme production. The obtained result was in agreement with previous reports for protease production from streptomycetes (Chaphalkar and Deys, 1998;Kim and Lee, 1995;Yeoman and Edwards, 1994). Increasing of the alkaline protease was reported by several workers using different sugars such as fructose (Sen and Satyanarayana, 1993) and lactose (Malathi and Chakraborty, 1991).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Temperature is an important environmental factor for growth and enzyme production. The obtained result was in agreement with previous reports for protease production from streptomycetes (Chaphalkar and Deys, 1998;Kim and Lee, 1995;Yeoman and Edwards, 1994). Increasing of the alkaline protease was reported by several workers using different sugars such as fructose (Sen and Satyanarayana, 1993) and lactose (Malathi and Chakraborty, 1991).…”
Section: Discussionsupporting
confidence: 83%
“…Streptomyces that produce protease include S. clavuligerus, S. griseus, S. rimosus, S. thermoviolaceus and S. thermovulgaris (James et al, 1991). They produce variety of extracellular proteases that have been related to aerial mycelium formation and sporulation (Kim and Lee, 1995). Studies on Streptomyces clavuligerus cultures for protease production showed that the amount of enzyme produced varies greatly with the culture media used (Porto et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…No other TLP proteases have been detected in S. antibioticus throughout the developmental cycle, although a serine protease of a chymotrypsin type has also been detected in the culture medium. 3 An enzyme with these characteristics was also detected in S. exfoliatus (35), and it was suggested that it participated in the utilization of external proteinaceous nitrogen sources. The S. antibioticus chymotrypsin-like protease shows a higher capability to degrade protein substrates than TLP.…”
Section: Discussionmentioning
confidence: 99%
“…Serine proteases, many with the characteristics of a TLP, have been described in other species of Streptomyces and related to aerial mycelium development (7, 34 -36). Inhibitors of TLPs, such as TLCK and leupeptin, impair the formation of aerial mycelium in S. albidoflavus (33), S. exfoliatus (35), and several other species of Streptomyces (36), which suggests the widespread distribution and critical role of these proteases in bacterial development. A TLP has been proposed to play a role in the metabolism of S. exfoliatus mycelial proteins (36).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to antibiotics, Streptomyces species liberate several extra cellular enzymes [17]. They produce variety of extra cellular proteases that have been related to aerial mycelium formation and sporulation [18]. In view of the above, the present work was under taken to study the effects of culture conditions on the production of extracellular proteases by S. albolongus and S. aburaviences, and also aimed at optimization of media composition, which has been predicted to play a significant role in enhancing the production of protease.…”
Section: Introductionmentioning
confidence: 99%